THE ANALYSIS OF FOOD QUALITY AND SERVICE QUALITY OF DUTA CATERING TOWARDS CUSTOMER SATISFACTION AND BRAND LOYALTY - ABDILLAH NATA PRASETYA, MUHAMMAD FARHAN; SETYANTO, REFIUS PRADIPTA; AFIF, NUR CHOIRUL (JOURNAL OF RESEARCH IN MANAGEMENT, 2018)
The study entitled "the effect of the quality of food and service atAmbassador catering towards customer satisfaction and brand loyalty".Type of this research is a case study with survey method using thequestionnaire as a data collection tool. Research is done in the cikarang.There are many types of businesses, such as restaurants, culinaryfoodstreet, foodcourt, etc. But one of the most popular in many people nowis the catering. One of the catering that I take as one of the objects of mythesis is the Ambassador of Catering. As Ambassador catering Cateringwas able to attract the interest of several companies. Because of the newstand for several years and experienced a significant increase in thephenomenon and become Ambassadors of the catering business. Basedon the above issues, this research was conducted to analyze the quality ofthe food and the perceived service quality to customer satisfaction andcustomer loyalty towards Ambassador catering. The respondents in thisstudy are the 176 respondents who came from employees of companieswho use the services Ambassador catering. The research of using SEM(Structural Equation Model) as a tool of analysis techniques. SPSSstatistics paid off device is used to analyze the data. The results ofhypothesis testing using a T-test is as follows: (1) Food quality has apositive influence on customer satisfaction. (2) Service quality has apositive influence on customer satisfaction. (3) Customer satisfaction has apositive influence on brand loyalty. (4) food quality has no significantinfluence on brand loyalty. (5) service quality has a positive influence onbrand loyalty.